AgNOR Quantity In Thyroid Follicule Cells During Experimental Hypothyroidism - Öner, Jale; Özercan, İbrahim; Kükner, Aysel (Fırat University, 2001)
Objective: Nucleolar organiser regions (NORs) are defined as nucleolar components containing a set of argyrophilic proteins, which are selectively stained by silver methods. AgNORs can be identified as black dots localised throughout the nucleolar area by silver method. They accumulate in highly proliferating cells. In this study, we aimed to observe the AgNOR staining in thyroid follicule cells during experimental hypothyroidism. Material and method: Hypothyroidism was induced in 30 days old male Wistar rats by intraperitoneally injections of propilthiouracil (10 mg/kg day) for 15 day. The thyroid specimens of this rats were stained by AgNOR tecnique and examined in light microscopy. Results: The results were evaluated statistically by Student t test. Eexperimental groups were compared with their controls about their AgNOR quantitiy. Conclusion: AgNOR quantity of experimental groups were higher than their control.

Amaç: Çekirdekçik düzenleme bölgeleri (NOR); gümüş metoduyla boyanan bir grup argirofilik proteini içeren çekirdek kısımlarıdır. AgNOR proteinleri, gümüş boyama yöntemiyle çekirdek içinde küçük koyu benekler halinde görülebilirler. Yüksek çoğalma erkinde olan hücrelerde bu bölgeler sayıca artış göstermektedirler.Bu çalışmada deneysel olarak oluşturulan hipotiroidizmde tiroid follikül hücrelerinde AgNOR sayılarını gözlemlemeyi amaçladık. Gereç ve yöntem: 30 günlük erkek sıçanlara, intraperitoneal olarak 15 gün boyunca 10mg/kg propiltiurasil verilerek hipotiroidizm oluşturuldu. Sıçanlardan alınan tiroid doku örnekleri AgNOR tekniği ile boyandı ve ışık mikroskopta incelendi. Deney grupları AgNOR sayıları bakımından, kontrolleri ile karşılaştırıldı. Bulgular: Sonuçlar istatistiksel açıdan Student t testi ile değerlendirildi. Sonuç: Deney gruplarının AgNOR sayısı kontrollerdekinden daha yüksek bulundu.
DENEYSEL HİPOTİROİDİZMDE TİROİD FOLİKÜL HÜCRELERİNDE AgNOR SAYILARI